STUDY OF IPAG60 PLANT PERFORMANCE RELIABILITY IN TREATING DIFFERENT PEAT WATER TO SUPPORT CLEAN WATER SERVICES IN PEATLAND AREAS - Sutapa, Ignasius Dwi Atmana (LIPI Press, 2017)
Surface water, including rivers, lakes or ponds, in peatland areas has specific characteristics. Generally, this type of water has high level of acidity, organic matter, and high concentration in several metalic ions, like manganese and iron. The content of organic matter is usually indicated by dark brown color of water. In term of quality, this water is not suitable to be used directly for covering daily needs, such as drinking, cooking, and bathing by the local people. IPAG60 was proven as a small scale plant which has a good ability for treating different types of peat water to produce clean water as per the standards. This plant gives alternative technology to support clean water services in peatland areas.